Clinical features of rhinovirus infection in hospitalized adult patients during the epidemic season 2017–2018 - M. A. Bichurina; L. V. Voloshchuk; A. Go; M. M. Pisareva; D. A. Guzhov (Журнал инфектологии, 2020)
Purpose. Rhinovirus infection has in the past been perceived as a disease capable of causing mild respiratory symptoms in most cases in children. Modern clinical and epidemiological studies have shown that rhinovirus infection in adults and children and has a moderate and severe course. The aim of this study was to conduct a clinical and laboratory analysis of cases of rhinovirus infection in adult hospitalized patients and evaluate the etiological role of rinoviruses in the epidemic season of 2017/18.Materials and methods. 1013 case histories of patients admitted to the hospital with a diagnosis of SARS were studied. These patients were taken nasopharyngeal swabs were investigated by PCR for the detection of respiratory pathogens. A positive result was obtained with rhinovirus infection of 51 patients.Results. Of the examined patients, 41,6% had influenza, 45,8% had no viruses and 12,6% had other viral infections, of which 40% were due to rhinovirus infection. Among them, young patients prevailed: the median age for men was 31,0 years, for women-27,5 years. The disease occurred in a moderate form – 78,8%, severe course was observed in 5,3% of patients and was accompanied by infectious and toxic shock. Most often the disease occurred with complications acute bronchitis – 22,1%, pneumonia joined in 15,7% of cases.Conclusion. rhinovirus infection ranks first (40%) among non-influenza causes of viral respiratory tract infection in the examined patients. It was registered mainly in young people. In most cases, it proceeded in a moderate form and had a complicated course, including pneumonia.